PENGARUH KEPEMIMPINAN DAN MOTIVASI KERJA TERHADAP KINERJA PEGAWAI PADA DINAS KEBUDAYAAN DAN PARIWISATA PROPINSI BANTEN - Rachmi Yulianti (Program Studi Administrasi Negara Universitas Serang Raya, 2015)
This study aims to determine whether there is significant influence between leadership and motivation on the performance of employees at the Department of Culture and Tourism Banten Three hypotheses were tested in this study, first, there are positive influence of leadership and motivation to work together on employee performance , secondly, the positive influence of leadership on employee performance. Third, the positive effect of work motivation on employee performance. This research population is all employees of the Department of Culture and Tourism Banten Province as many as 87 people, and samples taken amounted to 87 people. Research instrument data using three kinds of tools, namely a questionnaire using a scale model of Likers. The questionnaire drawn up by the construction of the various theories of data analysis done on the level of 95% the result is that significantly throughout the hypothesis that there is. So the results of this study informs that the variable Leadership and Motivation are two important factors in improving the performance of employees at the Department of Culture and Tourism of the Province of Banten